STRATEGI KOMUNIKASI LEMBAGA AMIL ZAKAT (LAZ) SWADAYA UMMAH DALAM MENINGKATKAN JUMLAH MUZAKKI DI PEKANBARU - Rahmi Hidayah; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The first one that established in Riau province is Lembaga Amil Zakat (LAZ) Swadaya Ummah. Due to big potential of zakat in Indonesia, especially in Pekanbaru made growth of Zakat Institution in Pekanbaru increased. It can be seen the number of branches National Zakat Institutionopened in Pekanbaru like Dompet Duafa, Rumah Zakat (RZ) and Program Keadilan Peduli Umat (PKPU). As increasing ofZakat Institution National,Lembaga Amil Zakat (LAZ) Swadaya Ummah should further enhance communication strategy in order to remain trusted by society in Pekanbaru. The purpose of this study is to examine the introduction of targeted strategy, media selection strategy, assessment strategy objectives and strategies message communicator role which is used by Lembaga Amil Zakat (LAZ) Swadaya Ummah in Pekanbaru.This research receipts qualitative methods, namely the collection of data obtained based on the fact data in the field through observations, interviews, and documentation. Subjects of this study consisted of 10 persons namely 1 deputy director, 4 fundraiser , 1 customer service, and 4 muzakki Lembaga Amil Zakat (LAZ) Swadaya Ummah that are selected by using purposive technique. To analyze the results of this study use interactive data analysis techniques, while data validity checking techniques through extension of participation and triangulation.The results showed that the communication strategyof Lembaga Amil Zakat (LAZ) Swadaya Ummah in terms of the introduction of goals of the entire Muslim society in Pekanbaru, the placement target is divided into three strategic segments, namely employment, education, and region. For further, the election of media is divided into mass media, face-to-face media and internet media, in order to reach all levels of society. The contents of the message delivered by Lembaga Amil Zakat (LAZ) Swadaya Ummah Pekanbaru is persuasive, educative and informativemessage. After the contents of the message was conveyed, then muzakki will see the role of communicators in the communication that includes the appeal of the source and credibility of the source. Based on the communication strategy that was undertaken by communicator, it was quite effective that can be seens from tending the growing number of muzakki every year.Keywords: Communication Strategy, Organization Ummah, Improved Muzakki